Volatilities in the interdependence between stock market, bond market, and foreign exchange market in Vietnam: An empirical investigation - Nguyen, Khac Quoc Bao (University of Economics Ho Chi Minh City, 2023)
This study analyzes volatilities in the relations between stock mar-ket, bond market, and foreign exchange market in Vietnam from April 2014 through December 2015. Particularly, we address the questions of whether there exist sudden changes in correlations be-tween the markets to respond to volatility shocks and whether these changes are temporary or extended. By using VAR(p) – FIEGARCH(1,d,1) – cDCC and PELT approaches in combination with a regression estimation with dummy variables, our empirical results validate the interdependence between the markets, which is found to vary over time. More importantly, volatility shocks give rise to sudden changes in their correlations, and at certain times these are long-lasting. Investors and policy makers in Vietnam should accordingly have due consideration of long-term spillovers.